Odpowiedzi

2010-03-17T19:10:06+01:00
-4a+2b-c+5a-4b+5c+3a=-4a+8a+2b-4b-c+5c=4a-2b+4c
a= -3 b= 6 c =¼
4*(-3)+6*(-2)+4*¼=-12-12+1=-24+1=-23
3 4 3
  • hels
  • Rozwiązujący
2010-03-17T19:11:09+01:00
-4a + 2b -c +5a -4b +5c +3a
-4a +5a +3a +2b- 4b -c + 5c = 4a -2b +4c

a= -3
b= 6
c= ¼
4a -2b +4c = 4 x (-3) -2 x 6 +4 x ¼ = -12 -12 + 1 = -24 + 1 = -23
3 2 3
2010-03-17T19:11:12+01:00
Redukcja wyrazów podobnych
-4a +2b-c+5a-4b+5c+3a=4a-2b+4c
obliczanie sumy algebraicznej ;
4 *(-3)+2*6+4*(jedna czwarta)=-12+12+1=1
wartość wyrażenia wynosi 1

2 1 2